KEKERASAN DALAM RUMAH TANGGA; SUATU TINJAUAN INTERAKSIONIS - Fakhri Usmita (SISI LAIN REALITA, 2017)
Domestic violence that is unique violence, especially cause offender and the victim are closely or have a bond. Using literature review especially with symbolic interactionist approach, this article would like to explain simply why someone who is "close", or (initially) loves each other, can do violence, even that is considered cruel, inhuman just because of trivial things. In an interactionist view, domestic violence can occur because of the interpretation of the actor against the situation he faces. The actor defines the situation he faces, and decides to be resolved by using force.